Expression and purification of recombinant protein NLI-IF from Escherichia coli - Phuong, Nguyen Duy; Tuteja, Najaren; Ham, Le Huy; Hoi, Pham Xuan (Academia Journal of Biology, 2012)
In order to investigate the expression level of NLI-IF (Nuclear LIM Interactor-Interacting Factor) transcription factor - encoding gene which involved in drought tolerance in rice and identiflied in vitro DNA - binding ability of NLI-IF, we expressed and purified recombinant protein NLI-IF from E. coli Rossetta. 1,3 kb NLI-IF - encoding sequence was cut from pGEMT/NLI-IF and inserted into EcoRI/XhoI site in MCS of expression vector pET28a. pET28a/NLI-IF was transformed into E. coli Rossetta. 52 kDa recombinant protein NLI-IF was expressed optimally in E. coli using 0.1 mM IPTG as an inducer, at 20oC, for 5 h. We were successful in purification of recombinant protein NLI-IF using Ni-NTA affinity chromatography systerm. Purified protein has an ability of binding, specifically, to anti-His-tag antibody in Westerrn blot assay.